2012
DOI: 10.1227/neu.0b013e318241801a
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Trigeminal Nerve Branches for Transovale Radiofrequency Thermolesion

Abstract: This method proved to be useful to determine the exact localization of individual subdivisions of the trigeminal nerve in anesthetized patients, making this procedure safer and more comfortable for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Percutaneous radiofrequency coagulation of the Gasserian ganglion is widely accepted worldwide as a minimally invasive technique for treatment of primary trigeminal neuralgia. However, the understanding and mastery of surgical details varies among different hospitals [13]. To establish and standardize an operation procedure that is efficacious, controllable, safe, and low cost are key tasks for clinical physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous radiofrequency coagulation of the Gasserian ganglion is widely accepted worldwide as a minimally invasive technique for treatment of primary trigeminal neuralgia. However, the understanding and mastery of surgical details varies among different hospitals [13]. To establish and standardize an operation procedure that is efficacious, controllable, safe, and low cost are key tasks for clinical physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous technological advances have been described to improve correct positioning of the needle for safer therapy, including transition from fluoroscopy to computed tomography (CT) guidance, three‐dimensional (3D) navigation techniques, and electrophysiological recordings including evoked potential confirmations [12–15]. Here we report a novel CT‐guided technique to block the V2 branch via a trans‐FR approach.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have proposed another method of functional localization with an antidromic conduction to localize the target, but the technique was done for patients under general anesthesia [4]. Previous cadaveric studies revealed a safe puncture depth of 6-10 mm above the foramen ovale [2,6,8].…”
Section: Discussionmentioning
confidence: 99%